Methotrexate plus ustekinumab versus ustekinumab monotherapy in patients with active psoriatic arthritis (MUST): a randomised, multicentre, placebo-controlled, phase 3b, non-inferiority trial. (January 2023) - Koehm, Michaela; Rossmanith, Tanja; Foldenauer, Ann C; Herrmann, Eva; Brandt-Jürgens, Jan; Burmester, Gerd R; Kellner, Herbert; Kiltz, Uta; Kofler, David M; Rech, Jürgen; Mojtahed-Poor, Sorwe; Jonetzko, Christin; et al.
Summary: Background: The role of methotrexate in combination with biological agents in patients with psoriatic arthritis remains unclear. The MUST phase 3b trial aimed to compare the efficacy of ustekinumab plus placebo with ustekinumab plus methotrexate in patients with active psoriatic arthritis. Methods: In this investigator-initiated, randomised, multicentre, placebo-controlled, phase 3b non-inferiority trial done in 22 centres in Germany, patients with active psoriatic arthritis received open-label ustekinumab and were randomly assigned (1:1) to masked concomitant therapy with placebo or methotrexate (ongoing or new). The primary outcome was non-inferiority of mean Disease Activity Score-28 joints (DAS28) at week 24 for ustekinumab monotherapy (ustekinumab plus placebo) versus ustekinumab combination therapy (ustekinumab plus methotrexate), stratified by previous methotrexate treatment. The key secondary analysis was non-inferiority of DAS28 at week 52. The primary analysis was based on a stratified van Elteren test with an α of 2·5% and a non-inferiority margin of 12·5% by Mann-Whitney estimator. Adverse events and serious adverse events were assessed. This study is registered with ClinicalTrials.gov, NCT03148860 . Findings: Between Jan 24, 2017, and April 12, 2021, 186 patients with active psoriatic arthritis were screened, of whom 173 (93%) patients were enrolled and randomly assigned (1:1) to receive concomitant methotrexate therapy (n=88) or placebo (n=85). 84 patients were receiving methotrexate at baseline, and 89 patients had no previous methotrexate treatment. 166 (96%) patients (87 in the ustekinumab plus methotrexate group and 79 in the ustekinumab plus placebo group) were included in the safety and efficacy analyses at week 24 (69 [42%] female; 97 [58%] male; mean age 48·2 years [SE 1·1]). Ustekinumab plus placebo was non-inferior to ustekinumab plus methotrexate in DAS28 at week 24 (2·9 [SD 1·31] vs 3·1 [1·42]); the stratified Mann-Whitney estimator for treatment comparison was 0·5426 (95% CI 0·4545–0·6307). Non-inferiority for ustekinumab plus placebo was also observed in DAS28 at week 52. Serious adverse events occurred in seven (9%) patients in the ustekinumab plus placebo group and eight (9%) patients in the ustekinumab plus methotrexate group. No specific serious adverse events affected more than one patient, and there were no deaths. Interpretation: Interleukin (IL)-12 and IL-23 inhibition with ustekinumab is an effective treatment for psoriatic arthritis independent of methotrexate use; concomitant methotrexate did not increase efficacy of ustekinumab (based on DAS28). On the basis of these data, there is no evidence to support the addition or maintainance of methotrexate when initiating ustekinumab in patients with active psoriatic arthritis. Funding: Janssen Cilag.